Heterozoan carbonates from the equatorial rocky reefs of the Galápagos Archipelago. Issue 4 (9th February 2016) - Reymond, Claire E.; Zihrul, Konny‐Sebastian; Halfar, Jochen; Riegl, Bernhard; Humphreys, Alexander; Westphal, Hildegard
Abstract: Strongly influenced by seasonal and interannual (i.e. El Niño‐Southern Oscillation) upwelling, the equatorial setting of the Galápagos Archipelago is divided into well‐defined temperature, nutrient and calcium carbonate saturation (Ωaragonite ) regions. To understand the relationship between oceanographic properties and sediment grain associations, grain size, carbonate content and components from sea floor surface samples were analysed, representing the main geographical regions of the Galápagos Archipelago. The shallow‐water rocky reefs of the Galápagos Archipelago are characterized by mixed carbonate–siliciclastic slightly gravelly sands. Despite minor differences in carbonate content, major differences exist in the distribution and composition of key carbonate producing biota. Halimeda is absent and benthic foraminifera occur in extremely low abundance. The western side of the Galápagos Archipelago is strongly influenced by nutrient‐rich, low‐Ωaragonite, subtropical water, which generates a heterozoan carbonate biofacies in a tropical realm resembling cold‐water counterparts (i.e. serpulid, echinoderm, gastropod, barnacle and bryozoan‐rich facies). The Central East region is composed of a transitional‐heterozoan biofacies. Biofacies observed in the northern region have an increased occurrence of tropical corals, albeit with a minor overall contribution to the carbonate components. Although the temperature gradient would allow for a broader distribution of photozoan biofacies, the increased nutrient concentration and related reduced light penetration from the upwelled waters favour heterozoan carbonate factories, mimicking cool‐water, deeper or higher latitude environments. The recent sedimentary record of the Galápagos Archipelago presents a range of tropical heterozoan carbonate communities, responding to more than simply latitude or temperature but a much more complex mixture of physical, evolutionary and geological processes.